A second look: improving safety perceptions of urban alleys - Aleman, Marcos (Kansas State University, 2020)
In the U.S., urban alleys often serve as rear access and service roads, but have been neglected as public spaces. The enclosed space of urban alleys attracts crime and other unwanted activity from the streets where it is less conspicuous. Many people perceive alleys as dangerous spaces or merely for parking vehicles outside of the adjacent buildings. This study looks at alleys as usable public space by mitigating people’s safety perception. The study purposes are: To identify physical elements within urban alleys that are most associated with perceptions of safety; to examine the alteration of physical elements related to safety perception; and, to propose a design framework that can be applied to practices found in this study to improve the human perception of alleys. In this study, twenty-four subjects participated in a survey using virtual reality environments that consist of eleven physical element variables selected from the literature review. The two elements that had the most negative perceptions was the presence of trash and unmaintained pavement, while one of the most positive perceptions was through the introduction of vegetation. Lighting and increased surveillance were also among the elements that improved perceptions of safety. Based on the results, a design framework was created for transforming alleys into viable and usable public space for more economic and social activity.
Improving safety perceptions of urban alleys: a virtual reality experiment
Keywords: Alley; Urban; Design; Virtual reality; Safety; Human perception